Assessing communicative-pragmatic ability in telehealth: e-ABaCo in autistic individuals - Traetta, Ilaria; Gabbatore, Ilaria; Aimar, Alessandra; Arduino, Giuseppe Maurizio; Bosco, Francesca M. (Frontiers in Psychiatry, 2025)
IntroductionAutism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by difficulties in social communication. Autistic individuals who are verbally fluent, often show difficulties in pragmatic ability, i.e. the capacity to use language and other expressive means, as gestures or the tone of the voice, to convey meaning in a given context. During the COVID-19 pandemic, the use of various technologies such as videoconferencing and internet for the delivery of healthcare services, i.e. telehealth, has proven to be effective, accessible and safe tools for remote healthcare. However, there are few tools to assess pragmatic skills in telehealth. This study investigates the effectiveness of the telehealth-adapted Assessment Battery for Communication (e-ABaCo), a clinical tool previously validated for in-person assessments, to evaluate pragmatic abilities in autistic individuals. We expect a substantial equivalence in performance for the administration of the adapted version of e-ABaCo compared to the face-to-face one.MethodsWe compared the performance of 30 autistic adolescents, of which 15 assessed via telehealth (ASD TH) and 15 assessed face-to-face (ASD FtF), with that of 15 adolescents with typical development (face-to-face assessment). The groups were matched for age, sex, and intellectual quotient. E-ABaCo was used to assess both comprehension and production of communicative ability realized through different expressive means, i.e. linguistic, extralinguistic and paralinguistic, as well as social appropriateness.ResultsIn line with the expectation, the pragmatic performance of autistic adolescents showed a substantial equivalence when comparing the assessments conducted via telehealth and face-to-face modality. Moreover, in line with the relevant literature, there was a significant difference between the ASD groups’ performance (both FtF and TH) and the control group of the adolescents with typical development (CG FtF) in all pragmatic aspects assessed, i.e. the Pragmatic total score, comprehension and production abilities, and all the expressive means investigated.DiscussionThese results confirm the potential usefulness of telehealth assessment procedures, and demonstrate the sensitivity and validity of e-ABaCo for conducting an effective assessment of pragmatic skills in on-line modality in autistic adolescents.